Pedagogies of Propaganda: The Role of Critical Articles in Shaping Social Consciousness During the Communist Regime - Axhami, Loreta; Nelku, Raimonda (European Journal of Social Science Education and Research, 2026)
This study analyzes the role of critical articles on feature films as propaganda instruments that served to form social consciousness during the communist regime in Albania from 1961-1990. The study employs a mixed-methods approach, combining quantitative analysis of articles on Albanian film (N=586) with qualitative data from structured interviews (N=10)) with critics, journalists, correspondents, and collaborators of Drita newspaper, one of the most influential cultural media outlets of the time. Also, the study used qualitative data derived from key documents, such as reports from the Congresses and Plenums of the Labor Party of Albania, the League of Writers and Artists, etc. The findings indicate that critical articles served not only to control and manipulate public opinion but also as a form of public education. This situation promoted censorship among creators and artists, leaving lasting consequences for how post-regime society perceives education, criticism, and authority. The study's findings may help prevent the resurgence of similar forms of control and manipulation of public opinion.
Keywords: Media Sociology, Propaganda, Public opinion, Ideology, Social consciousness, Censorship, Totalitarianism.